Reply to Comment on "Odd-parity excitons in semiconductor superlattices" - Meier, Torsten; Bott, K.; Hader, J.; Brinkmann, D.; Koch, S.W.; Thomas, P. (Physical Review B)
In his Comment on our work Glutsch raises, on the basis of a calculation for a dimerized three-dimensional superlattice, four points: (1) odd-parity excitons do not contribute to optical absorption, (2) there are no forbidden single-particle transitions, (3) there is a coupling of the e1-hh2 exciton (called ¯X in Ref. 1) to the underlying e1-hh1 continuum that leads to a Fano resonance, and (4) the extension of the exciton wave function is infinite in an all space directions rather than having a small extension. In this Reply these four points are addressed and it is shown that our previous conclusions remain valid.

Field-dependent absorption in superlattices: Comparison of theory and experiment - Meier, Torsten; Thränhardt, A.; Kolbe, H.J.; Hader, J.; Weiser, G.; Koch, S.W. (Applied Physics Letters)
Absorption and differential electroabsorption spectra of a GaInAs/InP superlattice in the regime of Wannier–Stark localization are compared with spectra derived from the Semiconductors Bloch Equations. The absorption is strongly underestimated for higher energies by the effective mass approximation but good agreement is achieved by using an energy dependent in-plane effective mass. No fitting parameters are used except for a phenomenological broadening. The lineshape of the field-modulated spectra is dominated by the strong field dependence of Wannier–Stark transitions and depends on the amplitude of the modulating field which should be kept small for best results. REFERENCES

Field-Induced Four-Wave Mixing Signal in Semiconductor Superlattices - Meier, Torsten; Je, K.-C; Kim, Y.; Koch, S.W. (Journal of the Korean Physical Society)
The four-wave mixing (FWM) signal of a semiconductor superlattice with an external electric field is evaluated using the semiconductor Bloch equations. It is found that the FWM signal for a GaAs/AlGaAs-semiconductor superlattices with a lattice constant d has a deep valley when the electric field is around eF d = 1 meV. It is also found that the deep valley comes mainly from the broken inversion symmetry caused by the exteral electric field and that the field intensity determines the sign and the magnitude of the Coulomb-induced optical nonlinearities.

Kultur, Kulturen, Gottesdienste. Öffentliche Inszenierung des Lebens. Festschrift für Peter Cornehl - Schroeter-Wittke, Harald (Pastoraltheologie)

Nach Ostern: Unsere Jesusbilder. Predigt zu Mk 12,28-34 - Schroeter-Wittke, Harald (Zeitschrift für Gottesdienst und Predigt)

Femtosecond Two Color Four-Wave Mixing Experiments on GaAs Quantum Wells Using Two Independently Tunable Lasers - Meier, Torsten; Yahng, J.S.; Ahn, Y. H.; Sohn, J.Y.; Koch, S.W.; Kim, D.S. (Ultrafast Phenomena XI)
Femtosecond four-wave mixing experiments on GaAs/AlGaAs quantum wells are performed with two independently tunable lasers. Many new results are found, including the heavy-hole-light-hole beating with these two mutually incoherent lasers.

Projective transformations of a plane - Burban, Igor; Duma, W. (U sviti Mathematyky)

Projective transformations of a plane and three-dimensional space - Burban, Igor; Duma, W. (U sviti Mathematyky)

Rational parameterization of algebraic curves - Burban, Igor (U sviti Mathematyky)

Politik und Bilder, Kulturrevolution

Positionierung und Visualisierung. Die ›Standorte‹ digitaler Bilder - Adelmann, Ralf (Ungleichheit als Projekt. Globalisierung – Standort – Neoliberalismus)

Satelliten, Fernsehen und Kontrollgesellschaft. Verstreute Hinweise zur Popularisierung neuer Visualisierungstypen, Adelmann, Ralf / Stauff, Markus (Hg.) - Adelmann, Ralf (Politik und Bilder. Kulturrevolution)

Anforderungen an den Religionslehrer und seine Ausbildung – schulpädagogische Perspektiven - Freitag, Christine (Aus der Arbeit der Studienseminare)

Undurchsichtigkeit und Kontexte als Herausforderung – Ansätze zu einer Metakritik. Ethik und Sozialwissenschaften - Blanck, B.; Herzig, Bardo; Loh, W. (Streitforum für Erwägungskultur EuS 9(1998)4)

Förderung ethischer Urteils- und Orientierungsfähigkeit. Grundlagen und schulische Anwendungen - Herzig, Bardo

Millionenschwere Medienverweigerer: Die US-Rockband Nirvana - Jacke, Christoph (Neues zum Umgang mit Rock- und Popmusik)

Nirvana - Der Anti-Star als Medienheld - Jacke, Christoph (Testcard. Beiträge zur Popgeschichte.)

Vertrauen: Voraussetzung oder Ergebnis effizienter Arbeitsbeziehungen?-Gutenbergs Solidaritätsaxiom und die institutionenökonomische Unternehmenstheorie. - Sadowski, Dieter; Pull, Kerstin; Schneider, Martin

Invariant Cones in Real Representations - Hilgert, Joachim; Neeb, K.-H. (Positivity in Lie Theory: Open Problems)

Reproducing Kernels on Vector Bundles - Hilgert, Joachim; Bertram, W. (Lie Theory and its Applications in Physics)